Toward a new conceptual framework: Employing a Black feminist approach to the recruitment and retention of Black women faculty in health and medical degree programs - Jeannette M Wade (Women's Health)
The sociodemographic makeup of the professoriate in health and healthcare has been shown to have direct implications for graduation rates among minoritized populations, diversity in healthcare, the prevalence of health equity scholarship, and population health broadly. Black women academics, who navigate higher education as members of two minoritized groups, need to be intentionally recruited and retained using tailored approaches. Given the historical and ongoing dearth of Black women faculty in health and healthcare, and the mounting literature on health equity highlighting the benefits of Black women representation in healthcare, I propose an approach to the recruitment and retention of Black women using a Black feminist theory. This conceptual framework outlines barriers to recruiting and retaining Black women faculty, as well as culturally tailored and gender-specific means to mitigate them, to create a safe space for Black women scholars to seek employment and thrive once they are there.